Battery management and energy control in hybrid grid - Fang, Yaxue (2012)
In nowdays we can see the energe costs are on the rise, carbon emissions and the environmental damage is getting worse, in order to better utilize the limit energy we have. We should do more research on energy management, as it can reduce these risks by monitoring, controlling and optimizing the performance of the generation and transmission system.